w=dependent variable
v=independendt variable
w(2v-w+1)dv+v(3v-4w+3)dw=0
"w(2v-w+1)dv+v(3v-4w+3)dw=0"
"(2vw-w^2+w)dv+(3v^2-4vw+3v)dw=0"
"M(v,w)=(2vw-w^2+w) \\implies {\\partial M(v,w) \\over \\partial w}=2v-2w+1"
"N(v,w)=(3v^2-4vw+3v) \\implies {\\partial N(v,w) \\over \\partial v}=6v-4w+3"
The differential equation is not exact since "{\\partial M(v,w) \\over \\partial w} \\not = {\\partial N(v,w) \\over \\partial v}"
There is no integrating factor of the form "p(v)" or "p(w)"
Let's try another method
"(2vw-w^2+w)dv+(3v^2-4vw+3v)dw=0"
"(2vw-w^2+w){dv\\over dv}+(3v^2-4vw+3v){dw\\over dv}=0"
"(2vw-w^2+w)+(3v^2-4vw+3v){dw\\over dv}=0"
"(2vw-w^2+w)+(3v^2{dw\\over dv}-4vw{dw\\over dv}+3v{dw\\over dv})=0"
"2vw-w^2+w+3v^2{dw\\over dv}-4vw{dw\\over dv}+3v{dw\\over dv}=0 ..........(i)"
Let "u=vw\\implies {du\\over dv}=w+v{dw\\over dv} \\implies {dw\\over dv}={{du\\over dv}\\over v}-{u\\over v^2}" and Substituting this to equation "(i)"
"2v{u\\over v}-({u\\over v})^2+({u\\over v})+3v^2({{du\\over dv}\\over v}-{u\\over v^2})-4v{u\\over v}({{du\\over dv}\\over v}-{u\\over v^2}) +3v({{du\\over dv}\\over v}-{u\\over v^2})=0"
The Variables cannot be separated further
Lets check if the differential equation is homogenous
"(2vw-w^2+w)+(3v^2-4vw+3v){dw\\over dv}=0"
"(3v^2-4vw+3v){dw\\over dv}=-(2vw-w^2+w)"
"{dw\\over dv}=-{(2vw-w^2+w)\\over (3v^2-4vw+3v)}"
The differential equation is not homogenous
"\\therefore" The differential equation has no solution
Comments
Leave a comment